2002
DOI: 10.1165/ajrcmb.26.2.4640
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Survival Factors Induce Akt Activation and Suppress Caspase-3

Abstract: A number of inflammatory cytokines and growth factors promote monocyte survival; however, the biochemical events stimulated by these factors are poorly defined. We previously showed that the monocyte survival factor macrophage colony-stimulating factor (M-CSF) activated monocyte survival through a PI 3-kinase-dependent pathway resulting in the phosphorylation of Akt and the suppression of the activation of caspase-3. Because other cytokines and bacterial cell wall products also induce monocyte survival, we hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 39 publications
6
76
0
Order By: Relevance
“…We previously observed that, whereas CpG DNA, LPS, and CSF-1 all efficiently activated ERK1/2, CpG DNA and LPS were relatively poor inducers of Akt phosphorylation compared with CSF-1 in BMM (45). Consistent with these findings in mouse macrophages, CSF-1 was also a more potent activator of Akt kinase activity than other survival factors, including LPS, in human monocytes (18). Despite these comparatively weak effects of bacterial products on Akt activation, we have shown that the PI3K inhibitor LY294002, which prevented Akt phosphorylation in BMM (data not shown), inhibited survival in response to LPS, CpG DNA, and CSF-1.…”
Section: Discussionsupporting
confidence: 68%
“…We previously observed that, whereas CpG DNA, LPS, and CSF-1 all efficiently activated ERK1/2, CpG DNA and LPS were relatively poor inducers of Akt phosphorylation compared with CSF-1 in BMM (45). Consistent with these findings in mouse macrophages, CSF-1 was also a more potent activator of Akt kinase activity than other survival factors, including LPS, in human monocytes (18). Despite these comparatively weak effects of bacterial products on Akt activation, we have shown that the PI3K inhibitor LY294002, which prevented Akt phosphorylation in BMM (data not shown), inhibited survival in response to LPS, CpG DNA, and CSF-1.…”
Section: Discussionsupporting
confidence: 68%
“…However, IFN-␤ treatment did not induce apoptosis, and the effect of LPS on apoptosis in macrophages is also still controversial (19,22). Recently, LPS was reported to induce apoptosis often in a cell type-specific manner and sometimes to show an antiapoptotic effect in monocytes, neutrophils, and macrophages (22,(31)(32)(33)(34). We also observed the similar results (LPS did not increase the apoptotic cell populations) in macrophages using flow cytometric analysis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…ERK, NFB-p50, JAK1, and AKT are key survival mediators, which are activated in response to inflammation and have previously been shown to inhibit caspase activation and promote monocyte differentiation (27)(28)(29)(30). Therefore, we examined the activation of these potential survival molecules by Western blotting.…”
Section: Characterization Of Cancer Cell-derived Exosomes and Theirmentioning
confidence: 99%